การศึกษาเทคนิคใหม่ในการเปลี่ยนโซเดียมซัลเฟตเป็น โซเดียมไฮดรอกไซด์และกรดซัลฟุริกด้วยเทคนิคอิเล็กโตรไลซิส - วิทย์ สุนทรนันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research concerns the study of the improvement of the electrochemical reactions at the cathode via an addition of oxygen in the form of dissolved oxygen into the solution at the cathodic side in achieving lower cell voltage for the separation of sodium sulphate solution using electrolysis technique with cation-exchange membrane. The purpose of oxygen addition is to replace the decomposition reaction of water by the combination of water and oxygen. The electrolysis cell was constructed and proper separating conditions were determined upon considering the concentrations of anodic and cathodic solutions and the current level employed. It was found that the concentration of anodic and cathodic solutions should not be lower than 1 and 0.2 N respectively while the current level should not fall below 1 A. The results of the experiments involving added oxygen at 10.5, 13.3 and 16.0 mg/l do not show any significant reduction of the cell voltage. This is probably because the amount of dissolved oxygen is too lowto yield a significant proportion of the combination reaction of water and oxygen in comparison to the decomposition reaction of water.